The Effectiveness of Dhikr Psychotherapy in Reducing Academic Anxiety Among Final-Year Students at Universitas Negeri Padang (UNP) - Farhan Arif; Nadila Salza Putri; Ashifa Putri Mahira; Hilya Qatrun Nailah; Hilmi Dzaki (CV. Causalita Dynamic Solutions, 2026)
Academic anxiety is one of the psychological problems frequently experienced by university students, especially those in the final stages of their studies. Pressure to complete a thesis, heavy academic workload, graduation requirements, and uncertainty about the future are the main factors contributing to the emergence of this anxiety. If not properly managed, it can lead to a decline in both mental health and motivation. Therefore, interventions are needed that not only address psychological aspects but also touch upon the students’ spiritual dimension.This study aims to determine the effectiveness of dhikr psychotherapy in reducing academic anxiety among final-year students. The research employs a quantitative approach with a pretest–posttest experimental design. The sample consists of final-year psychology students at Universitas Negeri Padang (UNP) who exhibited symptoms of anxiety based on initial screening results. The instrument used is the Academic Anxiety Scale (AAS). Data that had been tested for validity and reliability were then analyzed using the nonparametric one-sample Kolmogorov–Smirnov test for normality and the Wilcoxon signed-rank test to observe changes in anxiety scores before and after the dhikr intervention.